y = −2x + 8
y = x − 1

Explain how you will solve the pair of equations by substitution. Show all the steps and write the solution in (x, y) form.
Answer
5 (2 stars)
1
fieryanswererft 2 years ago
2391 response - 0 helps

Answer:

(3, 2)

Explanation:

  • y = −2x + 8 ....equation 1
  • y = x − 1 ....equation 2

======================

substitute equation 2 into 1

  • x − 1 = −2x + 8
  • x + 2x = 8 + 1
  • 3x = 9
  • x = 3

find y

  • y = x − 1
  • y = 3 − 1
  • y = 2

solution

  • (x, y) ⇒ (3, 2)
Answer
5 (2 stars)
1
semsee45 2 years ago
2792 response - 0 helps

Answer:

(3, 2)

Step-by-step explanation:

Given

Equation 1:  y = -2x + 8

Equation 2:  y = x - 1

Solving by Substitution

Substitute Equation 2 into Equation 1 and solve for x:

⇒ x - 1 = -2x + 8

Add 2x to both sides:

⇒ 3x - 1 = 8

Add 1 to both sides:

⇒ 3x = 9

Divide both sides by 3:

⇒ x = 3

Now substitute the found value of x into Equation 2 and solve for y:

⇒ y = 3 - 1

⇒ y = 2

Therefore, the solution is (3, 2)

Still have questions?